Freezing colloids : observations, principles, control, and use : applications in materials science, life science, earth science, food science, and engineering /: observations, principles, control, and use : applications in materials science, life science, earth science, food science, and engineering. (2017) - Deville, Sylvain, 1978-
No abstract available